2020
DOI: 10.1136/bmjopen-2020-037608
|View full text |Cite
|
Sign up to set email alerts
|

Trends and differences in sexual practices and sexually transmitted infections in men who have sex with men only (MSMO) and men who have sex with men and women (MSMW): a repeated cross-sectional study in Melbourne, Australia

Abstract: ObjectivesIn the 2010s, there has been an increase in sexually transmitted infections (STI) in men who have sex with men (MSM) in Australia, and since 2015 also in urban heterosexuals. Men who have sex with both men and women (MSMW) have characteristics that may differ from both men who have sex with men only (MSMO) and heterosexual men. We aimed to compare the sexual practices and the trends in HIV/STI positivity between MSMO and MSMW.DesignRepeated cross-sectional study.SettingA sexual health centre in Melbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…However, these data must be interpreted with caution as the number of women who reported intravenous drug use was small in our study (n = 254). Similar patterns can also be observed in studies defining WSW according to sexual orientation (i.e., lesbian, bisexual, or heterosexual); a 2013 Australian populationbased study (Roxburgh et al, 2016) demonstrated more than a fourfold higher odds of intravenous drug use among lesbian and bisexual women in comparison to heterosexual women, and similar patterns can be observed when comparing gay and bisexual men to heterosexual men (Martin-Sanchez et al, 2020a, 2020b, 2020cPhillips et al, 2019). These findings may be due to stigmatization associated with sexual minority status and social norms in the LGBTQIA + community (Corliss et al, 2006).…”
supporting
confidence: 62%
See 1 more Smart Citation
“…However, these data must be interpreted with caution as the number of women who reported intravenous drug use was small in our study (n = 254). Similar patterns can also be observed in studies defining WSW according to sexual orientation (i.e., lesbian, bisexual, or heterosexual); a 2013 Australian populationbased study (Roxburgh et al, 2016) demonstrated more than a fourfold higher odds of intravenous drug use among lesbian and bisexual women in comparison to heterosexual women, and similar patterns can be observed when comparing gay and bisexual men to heterosexual men (Martin-Sanchez et al, 2020a, 2020b, 2020cPhillips et al, 2019). These findings may be due to stigmatization associated with sexual minority status and social norms in the LGBTQIA + community (Corliss et al, 2006).…”
supporting
confidence: 62%
“…Prior to this time, only women who were symptomatic or who were contacts of a known gonorrhea case were offered gonorrhea screening at MSHC, meaning that a large number of asymptomatic women may have been missed. This is supported by a 2020 studying highlighting that up to half of cases of gonorrhea in women are asymptomatic (Martin-Sanchez et al, 2020a, 2020b, 2020c. Finally, limitations may have arisen due to the low numbers of WSWO in comparison to WSMO.…”
mentioning
confidence: 93%
“…In contrast to the increase in the notification rate of gonorrhea, there has been a decline in the HIV-1 notification rate from 4.5 to 4.0 per 100,000 population between 2013–2017 among MSM in Australia. Most of this reduction in HIV incidence can be attributed to the introduction of pre-exposure prophylaxis (PrEP) in 2016 [ 59 ].…”
Section: Epidemiology Of N Gonorrhoeae Infection and Disease In Australiamentioning
confidence: 99%
“…3 Recent Australian-based research found that there is no significant difference in urethral gonorrhoea positivity between men who have sex with men only and men who have sex with men and women, suggesting gonorrhoea transmission could subsequently be occurring between bisexual men and women. 4 Additionally, a study from a Melbourne centre found an increase in chlamydia positivity among lesbian women from no cases in 2011 to 2.7% in 2019 among those tested for STIs, 5 which raises questions regarding potential transmission of STIs from heterosexual populations by bisexual women to lesbian women, and whether sexual mixing has increased over a similar time period.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, these studies rarely examine whether bisexual men's partners are bisexual. 4 To the best of our knowledge, there have been very limited studies examining men and women having a partner who is bisexual. It is also unclear whether bisexual individuals are more likely to mix with other bisexual individuals than by random chance.…”
Section: Introductionmentioning
confidence: 99%